PATHWAYS TO POLITICAL ENGAGEMENT: Interviews with Social Workers in Elected Office - McLaughlin, Anne; Rothery, Michael; Kuiken, Jake (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2019)
In 2015, in an unexpected political upset, Alberta’s New Democratic Party was elected to govern for the first time in the province’s history. There were eight social workers amongst those elected, all of whom were interviewed for this research. The purpose of this qualitative study was to explore the motivations that led these social workers to seek political office, to identify factors in their personal and professional histories that explained their high level of political engagement, and to explore how the profession can increase the numbers of social workers pursuing political practice in the future. A standard qualitative thematic analysis of these interviews revealed that families of origin were influential motivators, and that social work education also played a significant role, as did professional experience and networks. Recommendations for change emerged from our findings. We discuss these with an emphasis on professional education and on what the academy can do to heighten levels of political engagement among future graduates.